Forging a Christian Order : South Carolina Baptists, Race, and Slavery, 1696-1860 - Kellison, Kimberly R., 1967- (Book collections on Project MUSE., 2023)
"This is a comprehensive examination of the Baptist movement in South Carolina from its founding to the eve of the Civil War. The author argues that from the beginning, the Baptist impulse and organization were driven by elites, who closely valued hierarchy and from the earliest times mounted a Christian defense of slavery. While the ideology of Baptists tended to emanate from the lowcountry, and there was some resistance to its details in the upcountry, Baptists ministers throughout the state fashioned a Christianized version of slavery that legitimized the institution"--